Pengaruh kinerja keuangan terhadap kebijakan dividen pada perusahaan sektor properti yang terdaftar di Bursa Efek Indonesia periode 2020-2024 - Kristianto Harikatan; Jantje J. Tinangon; Meily Y. B. Kalalo (Yayasan Widyantara Nawasena Raharja, 2026)
This study examines the effect of financial performance on dividend policy in property sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. Financial performance is proxied by Return on Equity (ROE), Current Ratio (CR), and Debt to Equity Ratio (DER), while dividend policy is measured using the Dividend Payout Ratio (DPR). The property sector is selected due to its capital-intensive characteristics, which make dividend distribution and profit retention critical managerial decisions. The sample consists of 10 property companies selected through purposive sampling, yielding 50 firm-year observations. Secondary data were analyzed using multiple linear regression. The results indicate that ROE has a positive and significant effect on DPR, suggesting that higher profitability increases firms’ capacity to distribute dividends. In contrast, CR and DER exhibit negative and significant effects on DPR, implying that higher liquidity and leverage encourage firms to retain earnings to support internal financing and debt obligations. The coefficient of determination (R²) of 0.923 indicates that the proposed model explains 92.3% of the variation in dividend policy. These findings highlight the trade-off between profitability, liquidity management, and capital structure in shaping dividend policy within capital-intensive industries such as property. The study provides important implications for investors and corporate managers in assessing the sustainability of dividend payments in the Indonesian property sector.